Factors Affecting Gen Z Brand Loyalty Toward E-Commerce Application - Pravyana, Kanishka; Soepatini, S (Universitas Muhammadiyah Surakarta, 2023)
Introduction/Main Objectives: The purpose of this paper is to determine the influence of brand awareness, perceived quality, perceived value, brand personality, organizational association, and brand uniqueness in E-commerce applications on consumer brand loyalty by examining the perception and loyalty of Gen Z in Indonesia towards the brands of E-commerce applications. Background Problems: This research is motivated by technological developments in E-commerce applications and the large number of E-commerce brands in Indonesia, which creates high competition. Novelty: This research focuses on the factors that influence Generation Z's loyalty to the many E-commerce application brands. Research Methods: In this research, the population is Gen Z, who use E-commerce applications for shopping. The data collection technique used a questionnaire that was distributed, and then 184 data were tested. The data analysis method uses multiple linear analyses. The data analysis method in this research was carried out using IBM SPSS Statistics version 26. Findings and Results: The research results show that for Gen Z in Indonesia, brand awareness, perceived value, organizational association, and brand uniqueness are influential factors in generating consumer loyalty towards E-commerce brands. Conclusion: The research results show that E-commerce service providers must use strategies to increase customer loyalty, such as building relationships with customers, guaranteeing that products sold on the platform are of good quality, and building brand uniqueness so they have an advantage over other E-commerce service providers.